Triazole‐Substituted Nitroarene Derivatives: Synthesis, Characterization, and Energetic Studies. Issue 1 (9th October 2013) - Kommu, Nagarjuna; Ghule, Vikas D.; Kumar, A. Sudheer; Sahoo, Akhila K.
Abstract A series of dense and energetic polynitroaryl‐1, 2, 4‐triazoles were synthesized through the nitration of aryl‐1, 2, 4‐triazoles. The Cu‐catalyzed/base‐mediated coupling reactions of haloarenes with 1, 2, 4‐triazoles delivered N‐aryl‐1, 2, 4‐triazoles. These new nitro‐rich‐aryltriazoles were characterized by analytical and spectroscopic methods. The solid‐state structures of most of these compounds were established by X‐ray diffraction analysis. Their thermal properties were determined by differential scanning calorimetry–thermogravimetric analysis. Their heats of formation (HOFs) and crystal densities were also calculated. The densities of the synthesized compounds ranged from 1.40 to 1.85 g cm−3. Some of these newly synthesized compounds exhibited high positive HOFs, good thermal stabilities, high densities, and reasonable detonation velocities and pressures.